2021
DOI: 10.3390/biomedicines9111626
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Vasculitis: An Overview

Abstract: Lupus vasculitis (LV) is one of the secondary vasculitides occurring in the setting of systemic lupus erythematosus (SLE) in approximately 50% of patients. It is most commonly associated with small vessels, but medium-sized vessels can also be affected, whereas large vessel involvement is very rare. LV may involve different organ systems and present in a wide variety of clinical manifestations according to the size and site of the vessels involved. LV usually portends a poor prognosis, and a prompt diagnosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 144 publications
(185 reference statements)
2
48
0
9
Order By: Relevance
“…Patients with systemic lupus erythematosus (SLE) were intentionally excluded in this study since they are more likely to develop both inflammatory and thrombotic (due to antiphospholipid syndrome) vasculopathies 35 . Therefore, evaluation of SLE vasculopathy is needed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with systemic lupus erythematosus (SLE) were intentionally excluded in this study since they are more likely to develop both inflammatory and thrombotic (due to antiphospholipid syndrome) vasculopathies 35 . Therefore, evaluation of SLE vasculopathy is needed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…LV normally appears during active disease and can be associated with APS. 26,27 The skin is affected in 90% of the cases. Less frequent is the involvement of the nervous system gastrointestinal tract, lungs, kidney, and heart.…”
Section: Discussionmentioning
confidence: 99%
“…As a complication of SLE, choroidopathy usually presents with single or multiple areas of serous detachment of the retinal pigment epithelium and neurosensory retina or retinal pigment epitheliopathy. The emerging choroidal effusion leading to anterior displacement of the lens–iris diaphragm may cause secondary angle-closure glaucoma with subsequent intraocular hypertension [ 51 ]. In 2019, an article was published that confirmed that the choroid in SLE patients appears to be thinner, particularly in the subset of patients with nephritis and taking anticoagulants, suggesting more advanced systemic vascular disease.…”
Section: Ophthalmic Manifestations Of Slementioning
confidence: 99%